IMPLIKASI AKAD MUSYARAKAH MUTANAQISAH PERBANKAN SYARI’AH - sutono sutono (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2020)
The development of Shari'ah Banking also encouraged the development of the products in it. One of the sharia banking products that is in great demand by the public is a housing finance product known as the Syari'ah Home Ownership Kongsi (KPRS). In its implementation, there are differences in several Islamic banks, namely using the murabahah and musyarakah mutanaqishah contracts. In 2008, the National Sharia Council issued a fatwa regarding the musyarakah mutanaqisah contract in financing home ownership. However, this contract has not been implemented by all Islamic banks. In 2012, Bank Indonesia issued a circular letter to all Sharia Banks and Sharia Business Units which further legitimized the implementation of the musyarakah mutanaqisah contract in Islamic banking. The Musyarakah mutanaqisah contract in KPR products will make it easier for customers to finance the KPR. The advantages of the musyarakah mutanaqisah contract for customers are a longer financing period and relatively cheaper installments.